2018
DOI: 10.1111/1749-4877.12343
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and oxytocin involvement in social preference in male mice: a study using a novel long‐term social preference paradigm with aromatase, estrogen receptor‐α and estrogen receptor‐β, oxytocin, and oxytocin receptor knockout male mice

Abstract: Certain aspects of social behavior help animals make adaptive decisions during encounters with other animals. When mice choose to approach another conspecific, the motivation and preference behind the interaction is not well understood. Estrogen and oxytocin are known to influence a wide array of social behaviors, including social motivation and social preference. The present study investigated the effects of estrogen and oxytocin on social preference using aromatase (ArKO), estrogen receptor (ER) α (αERKO), E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…CRISPR/Cas9 global knockout of OxTR in prairie voles decreases the ability to distinguish a novel mouse from a familiar mouse (Horie et al, 2019). In mice, both oxytocin and OxTR knockout impairs social preference and/or social memory (Ferguson et al, 2000;Tsuda et al, 2018). However, systemic injection of an OxTR antagonist does not affect social behavior with either novel or familiar same-sex mice (Haskal de la Zerda et al,…”
Section: Discussionmentioning
confidence: 99%
“…CRISPR/Cas9 global knockout of OxTR in prairie voles decreases the ability to distinguish a novel mouse from a familiar mouse (Horie et al, 2019). In mice, both oxytocin and OxTR knockout impairs social preference and/or social memory (Ferguson et al, 2000;Tsuda et al, 2018). However, systemic injection of an OxTR antagonist does not affect social behavior with either novel or familiar same-sex mice (Haskal de la Zerda et al,…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that when the odors of castrated and gonadally intact males were simultaneously presented in the preference test, sexually active male rats preferred that of the castrated one [ 53 , 54 , 55 ]. We considered it unlikely that the lack of testosterone (T) due to castration may newly produce an attractant for males, but that the lack of T disinhibits the negative feedback of the hypothalamus-pituitary-gonadal (HPG) axis, resulting in increased circulating levels of gonadotropin-releasing hormone (GnRH) and gonadotropins, and consequently, that those became male incentive odors.…”
Section: Sexual Stimuli Attributesmentioning
confidence: 99%
“…CD38 -/- mice demonstrate abnormal social memory and OT administration rescues it (Jin et al, 2007). And impaired social preference in oxytocin deficient mice may be due to severe deficits in social recognition (Tsuda et al, 2018). …”
Section: Oxytocin and Control Of Face Recognition In (Patho)physiologmentioning
confidence: 99%